An improved Suzuki–Miyaura cross-coupling reaction with the aid of in situ generated PdNPs: evidence for enhancing effect with biphasic system. Issue 29 (20th July 2016) - Mahanta, Abhijit; Mondal, Manoj; Thakur, Ashim Jyoti; Bora, Utpal
Graphical abstract: Highlights: Improved Suzuki–Miyaura reaction with in situ PdNPs in biphasic media is developed. The reaction is performed without using any conventional organic or inorganic base. The rice straw ash in aqueous media is acting as base in this reaction. An abundant agro waste is used as alternative base in Suzuki–Miyaura reaction. Chemical investigation of rice straw shows the presence K, Na, Li, Ca, and Mg metal. Abstract: We present here an improved Suzuki–Miyaura cross-coupling in WERSA (Water Extract of Rice Straw Ash). We found that, although the reaction can be run in neat water, use of alcoholic co-solvent dramatically enhances the yield and generates in situ PdNPs during the reaction. The PdNPs were characterized by TEM and powder XRD analysis. The rice straw ash was characterized by EDX, Flame photometry, and Ion-Exchange chromatography to reveal a broad range of active metal species. The chemical analysis reports of ash showed the presence of oxides of K, Na, and Ca, which probably in the presence of water produces the corresponding hydroxides responsible for the basicity.